Poor tuberculosis treatment outcomes in Southern Mozambique (2011–2012). Issue 1 (December 2016) - García-Basteiro, Alberto; Respeito, Durval; Augusto, Orvalho; López-Varela, Elisa; Sacoor, Charfudin; Sequera, Victor; Casellas, Aina; Bassat, Quique; Manhiça, Ivan; Macete, Eusebio; Cobelens, Frank; Alonso, Pedro
Abstract Background In Mozambique, there is limited data regarding the monitoring of Tuberculosis (TB) treatment results and determinants of adverse outcomes under routine surveillance conditions. The objectives of this study were to evaluate treatment outcomes among TB patients, analyze factors associated with a fatal outcome and determine the proportion of deaths attributable to TB in the district of Manhiça, Southern Mozambique. Methods This is a retrospective observational study based on TB patients diagnosed in the period 2011–2012. We used three different data sources: a) TB related variables collected by the National TB Control Program in the district of Manhiça for all TB cases starting treatment in the period 2011–2012. b) Population estimates for the district were obtained through the Mozambican National Statistics Institute. c) Deaths and other relevant demographic variables were collected from the Health and Demographic Surveillance System at Manhiça Health Research Center. WHO guidelines were used to define TB cases and treatment outcomes. Results Of the 1957 cases starting TB treatment in the period 2011–2012, 294 patients (15.1 %) died during anti-tuberculous treatment. Ten per cent of patients defaulted treatment. The proportion of patients considered to have treatment failure was 1.1 %. HIV infection (OR 2.73; 95 % CI: 1.70–4.38), being female (OR: 1.39; 95 % CI: 1.31–1.91) and lack of laboratory confirmation (OR 1.51; 95 % CI: 1.10–2.08) were associated with dying during the course of TB treatment (p value <0.05). The contribution of TB to the overall death burden of the district for natural reasons was 6.5 % (95 % CI: 5.5–7.6), higher for males than for females (7.8 %; 95 % CI: 6.1–9.5 versus 5.4 %; 95 % CI: 4.1–6.8 respectively). The age group within which TB was responsible for the highest proportion of deaths was 30–34 among males and 20–24 among females (20 % of all deaths in both cases). Conclusion This study shows a very high proportion of fatal outcomes among TB cases starting treatment. There is a high contribution of TB to the overall causes of mortality. These results call for action in order to improve TB (and TB/HIV) management and thus treatment outcomes of TB patients.